Pendidikan Akhlak Anak Kepada Orang Tua Dalam Perspektif Al-Quran Dan Hadits - Almer Ragil Amri; Muthia Azzahra; Intan Nuraini Azzahra; Revi Yulianti; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
As good Muslims, we certainly know that morals towards parents are very important. Because parents are the ones who introduce us to this world from childhood to adulthood. And every parent definitely has hopes for their child to be successful, dutiful to their parents, and become a better, more god-fearing child. The Al-Quran is a guide for human life in various fields and life situations experienced by each individual, including teaching the importance of doing good to both parents. One of the verses relating to doing good to both parents is found in the Al-Quran, Surah al-Ahqaf, verse 17. These verses explain the prohibitions and consequences for someone's happiness as a result of disobeying both parents, especially disobeying the mother, because of a mother's position. considered superior to a father. The purpose of this writing or research is to provide insight for parents and children about how to play an active role in building noble character based on the Koran and hadith. The method used in this research is a descriptive qualitative approach, using bibliographic/reference studies related to the interpretation of the Al-Quran regarding verses about being good to parents. The results of this research show that the role and attention of parents has a big influence in shaping and molding children into human beings with noble character whose actions and thoughts are in line with Islamic teachings.